Evaluating the role of environmental concern, risk perception and stakeholder salience in driving sustainable water consumption within sustainability project initiatives in the UAE hospitality sector - ElShafei, Rasha Abd El Nafea (2017)
The global water scarcity problem and unsustainable water consumption hinders the realisation of sustainability goals, therefore, the aim of this thesis is to empirically examine the influence of individual and stakeholder factors on the success of sustainability project initiatives in relation to sustainable water consumption in the UAE hospitality sector. Within a quantitative research approach, individual determinants of sustainable water consumption were identified. Stakeholder action framework is developed and designed as a questionnaire in an effort to collect and statistically analyse data from managers in UAE hospitality sector. The results indicate that individual determinants were significantly associated with sustainable water consumption strategies and practices. Albeit, the role of stakeholders salience attributes were critically important in this association. A significant positive influence on the association was shaped by power, urgency and legitimacy attributes. Moderation effect was manifested by the urgency and legitimacy attributes. Government and business stakeholders were the most salient stakeholders whereas; customers’ saliency was not detected. This thesis shifts sustainability research focus from individualistic paradigm to stakeholder paradigm. Findings will be cornerstone in achieving sustainability goals as it guides on factors contributing to sustainability project initiatives success. The study is limited to UAE hospitality sector; therefore, generalisation of results to other sectors is challenged.